Analisis Yuridis Terhadap Implementasi Peranan Hukum Dalam Pembangunan Ekonomi Masyarakat Kabupaten Kepulauan Yapen - Ebzon Y. Sembai (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Law has a very important position in the effort to achieve provide conditions that can spur the growth of economic development and to maintain relations between various elements and economic actors. The role of law in the economic development of a country is basically inseparable from discussion of the economic approach to law or vice versa, legal approach to economics, commonly known as economic analysis law. The economic approach to law means the use of economic considerations to solve problems, and the use of tools or concepts of analytical techniques commonly used by economist. The economic legal approach is of a nature and uses an approach transnational and interdisciplinary approach, specializing in the relationships between national economic and social problems and regional and international in an integral manner. There are at least five legal qualities which is conducive to development planning and implementation, namely: stability (stability, predictability, fairness, education, the special development abilities of the lawyer. We have prepared this scientific thesis proposal to the best of our ability and have received assistance from various parties so that it can facilitate the preparation of the Proposal This thesis. For that we express our many thanks to all parties who have contributed to the making of this Thesis Proposal. Apart from all that, We are fully aware that there are still shortcomings in terms of structure. sentences and grammar. Therefore, with open arms we accept all suggestions and criticisms from readers so that we can improve This scientific thesis proposal. Finally, we hope that this scientific thesis proposal on "Legal Analysis of the Implementation of the Role of Law in "Economic Development of the Yapen Islands Regency Community" can provide benefits and inspiration to ourselves personally and to others reader.